SSR markers reveal diversity in Guinea yam (Dioscorea cayenensis/D. rotundata) core set - Obidiegwu, J.E.; Kolesnikova-Allen, M.; Ene-Obong, E.E.; Muoneke, C.O.; Asiedu, Robert (2009)
The genetic diversity of 219 accessions of Guinea yam germplasm from Benin, Congo, Côte d’ Ivoire,Equatorial Guinea, Gabon, Ghana, Nigeria, Sierra Leone and Togo was accessed using 15 microsatelliteloci. High diversity of 0.677 was found among the accessions. An allelic average of 8.06 andpolymorphic information content (PIC) value of 0.65 was observed for the markers. The observedheterozygosity value of 0.563 suggests that spontaneous hybridization must have contributed to theancestry of some of the accessions and improvement by farmers must have been far more often byselection of somatic mutants. The twenty distinct cluster groups generated by the radial phylogramshows that Dioscorea cayenensis and D. rotundata are distinct species with intermediate hybrid forms.There was no relationship between relatedness of the accessions and their geographical area of origin.This study contributes to an increased understanding of the genetic organisation of the coregermplasm.